Postural Control in Lowlanders With COPD Traveling to 3100 m: Data From a Randomized Trial Evaluating the Effect of Preventive Dexamethasone Treatment - Muralt, Lara; Furian, Michael; Lichtblau, Mona; Aeschbacher, Sayaka S.; Clark, Ross A.; Estebesova, Bermet; Sheraliev, Ulan; Marazhapov, Nuriddin; Osmonov, Batyr; Bisang, Maya; Ulrich, Stefanie; Latshang, Tsogyal D.; et al. (Frontiers in Physiology, 2018)
Objective: To evaluate the effects of acute exposure to high altitude and preventive dexamethasone treatment on postural control in patients with chronic obstructive pulmonary disease (COPD). Methods: In this randomized, double-blind parallel-group trial, 104 lowlanders with COPD GOLD 1-2 age 20–75 years, living near Bishkek (760 m), were randomized to receive either dexamethasone (2 × 4 mg/day p.o.) or placebo on the day before ascent and during a 2-day sojourn at Tuja-Ashu high altitude clinic (3100 m), Kyrgyzstan. Postural control was assessed with a Wii Balance BoardTM at 760 m and 1 day after arrival at 3100 m. Patients were instructed to stand immobile on both legs with eyes open during five tests of 30 s each, while the center of pressure path length (PL) was measured. Results: With ascent from 760 to 3100 m the PL increased in the placebo group from median (quartiles) 29.2 (25.8; 38.2) to 31.5 (27.3; 39.3) cm (P < 0.05); in the dexamethasone group the corresponding increase from 28.8 (22.8; 34.5) to 29.9 (25.2; 37.0) cm was not significant (P = 0.10). The mean difference (95% CI) between dexamethasone and placebo groups in altitude-induced changes (treatment effect) was -0.3 (-3.2 to 2.5) cm, (P = 0.41). Multivariable regression analysis confirmed a significant increase in PL with higher altitude (coefficient 1.6, 95% CI 0.2 to 3.1, P = 0.031) but no effect of dexamethasone was shown (coefficient -0.2, 95% CI -0.4 to 3.6, P = 0.925), even when controlled for several potential confounders. PL changes were related more to antero-posterior than lateral sway. Twenty-two of 104 patients had an altitude-related increase in the antero-posterior sway velocity of >25%, what has been associated with an increased risk of falls in previous studies. Conclusion: Lowlanders with COPD travelling from 760 to 3100 m revealed postural instability 24 h after arriving at high altitude, and this was not prevented by dexamethasone. Trial Registration:clinicaltrials.gov Identifier: NCT02450968.